The relationship advantage information technologies, sourcing, and management - Kern, Thomas; Willcocks, Leslie (Oxford Oxford University Press, 2001)
An insight for both practitioners and academics on how to achieve a relationship advantage, this text examines five case studies, identifying the key dimensions of an outsourcing relationship
Title from title screen (viewed October 27, 2023)
Electronic reproduction
Keywords: Relationship marketing -- Case studies; Electronic data processing departments -- Case studies; Information technology; Contracting out